Status Hara N, P dan K serta Produktivitas Tanaman Karet Pada Dua Tapak Lahan Berbeda - Muhammad Wahyudi; Syaifuddin Syaifuddin; Ismed Fachruzi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Rubber plant productivity is often hampered because the availability of nutrients in the soil is not sufficient for plant needs. Some rubber productivity results in Karang Intan Village only reach 1,500-2,000 kg.ha-1.th-1 and some reach 2,000-3,000 kg.ha-1.th-1. Generally, the maximum yield of superior latex clones reaches 2,500-3,000 kg.ha-1.th-1. Given this background, it is necessary to conduct this research with the aim of knowing the status of N, P and K nutrients at location A (low productivity) and location B (high productivity). This research was carried out from July to September 2021. Sampling used in this research was purposive sampling method, sampling was conductedin Karang Intan Village, Kuranji District, analyzed of soil sample was at the Soil Physics and Chemistry Laboratory, Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, after that the data obtained from the results of the analysis categorized the level of fertility. The results showed that the Total-N, Total-P, Available-P, Total-K, Available-K in Locations A and B were not significant (Ortogonal Contrast Anova) so that these nutrients could not be used as factors that caused differences in rubber plant productivity. Ammonium and nitrate in Location B is higher than Location A, the difference in these values ​​is a factor that causes differences in the productivity of rubber plants in Karang Itan Village, Kuranji District.